Financial Constraints of Firms with Environmental Innovation - Febi Jensen; Dorothea Schäfer; Andreas Stephan (Vierteljahrshefte zur Wirtschaftsforschung, 2019)
Using the Mannheim Innovation Panel, we explore whether Environmental Innovator Firms (EIFs) have higher financial needs and are more financially constrained than Non-Environmental Innovator firms (OIFs). We find that EIFs are more likely to have higher latent financial need in comparison to OIFs. This implies that EIFs have latent projects that they have not yet realized, but would implement if they had the financial means to do so. EIFs adopting environmental technologies have higher financial needs compared to firms that do not. One tentative conclusion from this finding is that public subsidies might mitigate the financial restrictions of environmental innovation. – – Anhand des Mannheimer Innovationspanels untersuchen wir, ob Umweltinnovatoren (Environmental Innovator Firms, EIFs) einen höheren Finanzbedarf haben und finanziell stärker eingeschränkt sind als Nicht-Umweltinnovatoren (Non-Environmental Innovator Firms, OIFs). Unser empirischer Befund besagt, dass Firmen, die Umwelttechnologien einsetzen mit größerer Wahrscheinlichkeit einen latenten Finanzbedarf aufweisen, als Nicht-Umweltinnovatoren. Dies bedeutet auch, dass Umweltinnovatoren über latente Projekte verfügen, die sie noch nicht realisiert haben, die sie jedoch umsetzen würden, wenn sie die finanziellen Mittel dazu hätten. Eine vorläufige Schlussfolgerung aus diesem Befund ist, dass öffentliche Subventionen die finanziellen Beschränkungen von Umweltinnovationen mildern könnten.
Keywords: G30; D22; O31; 330; Environmental innovation; innovation capability; funding gaps; financing restrictions